A qualitative exploration of substance misuse among homeless women in Addis Ababa, Ethiopia - Haile, Kibrom (BMC Psychiatry, 2020)
BACKGROUND: Substance use among homeless people is higher compared to the general population. In some studies, reported rates of problematic drug use among the homeless vary, with estimates ranging from 25 to 70%. There is a common perception that substance abuse and homelessness are linked, but there is considerable debate about the direction of the relationship. Despite observations of high levels of substance use among the homeless population in Addis Ababa, there are limited studies to date conducted on the topic. This study aims to explore the factors associated with onset of substance use and its continued use, patterns of substance use and its social and health consequences among female residents of a shelter in Addis Ababa, Ethiopia. METHODS: A qualitative study was conducted in 2019. In-depth interviews were conducted on 14 study participants who were selected purposively. The qualitative data analysis software QDA Miner 5.0.30 was used for data processing and analysis. RESULTS: Four major thematic areas were identified and they comprised the categories under which sub-themes were identified and coded. The major segments or categories included the following: reasons for the onset of substance use after becoming homeless, experiences of substance use and reasons for continued use, the harms which resulted on them from substance use, and the means of obtaining supply of the substances. CONCLUSION: Factors related to life on streets were strong reasons for onset of substance use, as well as for its continued use. Homeless women suffered untimely death, addiction, and ill health from use of substances; however, they gave priority to obtaining substances than any other thing, and used every means to grab a supply of the substances.